Urinary Neutrophil Gelatinase-Associated Lipocalin Can Predict the Efficacy of Volume Expansion Therapy in Patients With Hepatitis B Cirrhosis and AKI - Zhonghui Duan; Minjie Jiang; Xiaojie Huang; Haixia Liu; Hongwei Yu; Qinghua Meng (Frontiers Media S.A., 2022)
Backgrounds: Kidney biomarkers in urine appear to be useful in differential diagnosis between acute tubular necrosis and other types of acute kidney injury (AKI) in cirrhosis. In clinical practice, prerenal azotemia (PRA) is often distinguished from other types of AKI by volume expansion therapy. The aim of the current study was to investigate the accuracy of urinary biomarkers in the differential diagnosis between PRA and other types of AKI.Methods: A total of 65 patients with hepatitis B cirrhosis were prospectively included and divided into AKI and non-AKI groups. Patients with hepatitis B cirrhosis and AKI discontinue diuretics, vasodilators, and nephrotoxic drugs and give volume expansion therapy. The efficacy was judged after 48 h of treatment. Urinary biomarkers were measured at the time of diagnosis of AKI and 48 h after volume expansion therapy. Univariate and multivariate analyses were used to identify independent risk factors for nonresponse to volume expansion therapy.Results: Of the 65 patients, 49 patients with newly diagnosed AKI were screened in the study, and 16 hospitalized patients with hepatitis B cirrhosis without AKI at the same period were screened as the control group. In patients with cirrhosis and AKI, 29 (59.18%) patients were in the response group and 20 (40.81%) patients were in the nonresponse group. The mortality rate in the nonresponse group was significantly higher than that in the response group (75% vs. 13.8% p < 0.001). After logistic regression analysis, urinary neutrophil gelatinase-associated lipocalin (NGAL) and serum creatinine (SCr) at diagnosis of AKI showed significant association with nonresponse to volume expansion therapy. The cutoff values for SCr and urinary NGAL were 128.50 µmol/L and 90.75 ng/ml, respectively. The area under the receiver operating curve (AUC) for SCr and urinary NGAL was 0.815 and 0.831.Conclusion: Elevated urinary NGAL can reflect the degree of kidney injury and is an independent risk factor for nonresponse to volume expansion therapy in patients with hepatitis B cirrhosis and AKI.